Study on the Treatment of Aluminum Milling Wastewater by Electrode-Fenton Method. Issue 4 (May 2019) - Li, Ru; Wang, Peng; Gu, JunLi
Abstract: Aluminum alloy chemical milling wastewater is the wastewater produced in the washing process after aviation aluminum chemical milling. According to its characteristics of high alkalinity, high concentration of organic compounds and difficult biochemical treatment, the electro-Fenton method was used in this study. Electro-Fenton method mainly is the Fenton reaction between Fe 2+ and hydrogen peroxide produced by electrolytic dissolved oxygen to produce HO⋅, which reacts with organic pollutants and mineralizes. In the experiments, activated carbon fiber and Ti/RuO2 – IrO2 were used as the cathode and the anode, respectively. The experiments showed that the optimal initial pH value of degradation was 3, voltage was 40V, and the concentration of Fe 2+ was 0.5mmol/L, plate spacing was 5cm, the concentration of Na2 SO4 was 10g/L, the aeration intensity was 125L/h, and the reaction time was 120min, the average removal rate of COD was over 50%. Under optimum conditions, the study established a dynamic model and educed that it could be described with first order dynamic model. The fitting equation is: Cr = C0 exp(-1.2879 C 0 −0.8253 t ).